Mental health in ‘low-to-moderate risk’ preterm, low birth weight and small for gestational age children at 4-5 years: The role of early maternal parenting. - Westrupp, E (My University, 2011)
Objectives: The majority of children born preterm, low birth weight or small for gestational age are born with low-to-moderate risk (LTM), yet most research focuses on the high-risk group. Little is known about whether children with LTM perinatal risk are at greater risk of mental health problems, or the role of early maternal parenting in determining these outcomes. Methods: Longitudinal data were from a large nationally representative Australian cohort of 5,000 children, aged 0-1, 2-3 and 4-5 years of age. Participants were 354 children with LTM perinatal risk (born <37 and >32 weeks gestation, birth weight <2,500 and >1500 g, or <10th and >1st percentile for gestational age) and 2,461 children in the normal birth weight, term comparison group. Child mental health was measured using maternal-reported total difficulties on the Strengths and Difficulties Questionnaire (SDQ). Parenting irritability, warmth, self-efficacy, maternal separation anxiety and overprotective parenting were measured when children were age 0-1 and 2-3. Results: Parents in the LTM perinatal risk group were more likely to experience parenting difficulties on 1 of 8 parenting measures (irritable parenting at age 0-1) when adjusting for socio-demographic differences (OR = 1.43; 95% CI = 1.05, 1.95, p<0.02). This group difference was no longer apparent by age 2-3. LTM perinatal risk group membership predicted mental health problems on the SDQ at age 4-5 in the unadjusted model but not when accounting for maternal-specific and socio-demographic differences. Conclusions: Children with LTM perinatal risk did not significantly differ in their mental health from other children of similar social backgrounds. These findings support an environmental, rather than parenting, pathway to psychological risk in children born with LTM perinatal risk.
Keywords: Children -- Babies; Families -- Parents and Parenting; Families and relationships; Families; Children; Babies; Parents and Parenting; Families and relationships